Taxation for universities and colleges : six steps to a successful tax compliance program - Hoffman, Steve, 1950- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2013)
"The "Tax Translator" offers much needed advice and guidance on tax compliance for institutions of higher learning. College and university officials often are unaware of their institutions' tax obligations. Especially for institutions without designated tax compliance officers, the consequences of such ignorance can devastating. Based on its author's decades of experiences as a tax manager at three universities, this handbook was written for all university staff involved with tax compliance--from the account clerk in the Accounts Payable Department, up through vice presidents, controllers, treasurers and directors. Steve Hoffman explains the core principles and practices that inform current tax policy and develops a framework for building a system for effective tax compliance, reporting and filing. Satisfies the urgent demand for timely, authoritative advice and guidance on a area of increasing concern for colleges and universities Sheds new light on the impact of current tax obligations for both four-year and community colleges, which are often left out of the discussion The Federal Government has recently stepped up its enforcement of tax law compliance for colleges and universities "--
What a VP Wants From a Tax ManagerA Tax Translator Guide to Ubit Determination; Ubit Compliance Checklist; Unrelated Business Income; Foreign Activities; Other State Activities; Activities/Expenditures; University of Central Florida Ubit Questionnaire; University of Notre Dame Ubit Questionnaire; Index
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Universities and colleges -- Taxation -- Law and legislation -- United States; BUSINESS & ECONOMICS -- Taxation -- General; Universities and colleges -- Taxation -- Law and legislation; United States; Electronic books